Risk of intracerebral haemorrhage in Chinese patients with atrial fibrillation on warfarin with cerebral microbleeds: the IPAAC-Warfarin study. Issue 4 (15th December 2018) - Soo, Yannie; Abrigo, Jill M; Leung, Kam Tat; Tsang, Suk Fung; Ip, Hing Lung; Ma, Sze Ho; Ma, Karen; Fong, Wing Chi; Li, Siu Hung; Li, Richard; Ng, Ping Wing; Wong, Kwok Kui; et al.
Abstract : Background and purpose: Cerebral microbleeds (CMBs), which predict future intracerebral haemorrhage (ICH), may guide anticoagulant decisions for atrial fibrillation (AF). We aimed to evaluate the risk of warfarin-associated ICH in Chinese patients with AF with CMBs. Methods: In this prospective, observational, multicentre study, we recruited Chinese patients with AF who were on or intended to start anticoagulation with warfarin from six hospitals in Hong Kong. CMBs were evaluated with 3T MRI brain at baseline. Primary outcome was clinical ICH at 2-year follow-up. Secondary outcomes were ischaemic stroke, systemic embolism, mortality of all causes and modified Rankin Scale ≥3. Outcome events were compared between patients with and without CMBs. Results: A total of 290 patients were recruited; 53 patients were excluded by predefined criteria. Among the 237 patients included in the final analysis, CMBs were observed in 84 (35.4%) patients, and 11 had ≥5 CMBs. The mean follow-up period was 22.4±10.3 months. Compared with patients without CMBs, patients with CMBs had numerically higher rate of ICH (3.6% vs 0.7%, p=0.129). The rate of ICH was lower than ischaemic stroke for patients with 0 to 4 CMBs, but higher for those with ≥5 CMBs. CMB count (C-index 0.82) was more sensitive than HAS-BLED (C-index 0.55) and CHA2DS2-VASc (C-index 0.63) scores in predicting ICH. Conclusions: In Chinese patients with AF on warfarin, presence of multiple CMBs may be associated with higher rate of ICH than ischaemic stroke. Larger studies through international collaboration are needed to determine the risk:benefit ratio of oral anticoagulants in patients with AF of different ethnic origins.